Design-ability in the Circular Economy of Textiles - Andersen, Kirsti Reitan; Skjold, Else; Nyvang, Linda; Bang, Anne Louise; Larsen, Astrid Tolnov; Harsaae, Malene Pilgaard; Jørgensen, Poul-Erik (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Recent research underscores the importance of longevity, defined as the combination of high and long-term usage frequency and durability, in the textile and fashion industry’s shift toward circularity and sustainability. This paper explores and discusses the designer’s ability to design for longevity of textiles. Thus, focus is on the potential role of textile designers, examining the extent to which the skills and competencies of the designer may potentially have an actual influence on longevity. Additionally, the paper discusses the systemic context that creates opportunities for design to contribute to the longevity of textiles and garments. Theoretically, the paper draws on Young’s framework of levels of context—specifically design in context and designing context—as well as Pineda et al.’s emphasis on the relationship between contexts and the designed object. Empirically, the study is based on data collected from an ongoing research project, [Project X], in which a consortium of academic institutions and industry partners explores opportunities for textile recovery through material-led experiments with recycled textile fibres, further processed in a local R&D factory setup. This paper demonstrates that the challenges of recycling extend beyond design strategies and material experiments, encompassing cultural perceptions and the opportunities available to designers. Furthermore, by highlighting the competencies required to facilitate relationships and collective knowledge building through textile prototypes, the paper supports previous research suggesting that designers play a central role in the transition toward sustainability.